High-performance solid-state battery containing CPL-LCF composite lithium metal negative electrode material and preparation method of high-performance solid-state battery
By forming a protective layer on the surface of the lithium metal negative electrode of the lithium battery and using Si/C composite negative electrode material and CaLi2 alloy, the cycle stability and safety of the negative electrode material of the lithium battery are solved, and the energy density and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202510082803.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The theoretical specific capacity of graphite anode material of traditional lithium-ion batteries is lower, and there are problems with the cycle stability and safety of lithium metal anode, which affects its application.
The CPL-LCF composite lithium metal negative electrode material is used to form a protective layer on the surface of the lithium foil to prevent contact of the lithium negative electrode and the electrolyte. The electrochemical performance and structural stability of the negative electrode material are improved by adding Si/C composite negative electrode material and CaLi2 alloy.
It improves the energy density, electrochemical performance and structural stability of lithium batteries, reduces the generation of lithium dendrites and the volume changes of lithium negative electrodes, and enhances the safety of the battery.
Smart Images

Figure CN119905673A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-performance solid-state battery containing a CPL-LCF composite lithium metal negative electrode material and a preparation method thereof, belonging to the technical field. Background Art
[0002] With the increasingly serious environmental damage brought about by global economic development, people are becoming more and more aware of the importance of ecological protection. Therefore, clean and renewable solar energy, wind energy, tidal energy, etc. have been vigorously developed. The continuous improvement of the energy structure has also driven the research and development of high-energy, high-power energy storage devices. Due to the advantages of high operating voltage, high specific energy, and long cycle life, lithium-ion batteries (LIBs) have been widely used in portable electronic devices and automobiles. In recent years, safety accidents such as fire and explosion caused by lithium-ion battery electrolyte leakage and internal battery short circuit have occurred frequently. Solid-state batteries are composed of intrinsically safe solid materials (solid-state electrodes, solid-state electrolytes), and are also used for the use of lithium metal negative electrodes. It provides an opportunity to realize high energy density lithium batteries.
[0003] The theoretical specific capacity of traditional graphite negative electrode materials is only 372 mAhg –1 , which is difficult to meet the needs of high energy density battery development. Lithium metal has the lowest redox potential and has the advantages of high theoretical specific capacity and low density compared to standard hydrogen electrodes, which has attracted widespread attention. An ideal high-performance solid-state battery should have the following characteristics: (1) high energy density (2) excellent safety (3) good electrochemical performance (4) high ionic conductivity. Metal lithium anode is an ideal high energy density anode material, with a specific capacity up to ten times that of graphite anode. However, the growth of lithium dendrites, the side reactions between lithium anode and electrolyte, and the large volume change during charge and discharge seriously affect its cycle stability and safety performance, hindering the application of lithium anode. By forming a protective layer on the surface of lithium anode through coating modification, the lithium anode can be prevented from contacting with the electrolyte, while uniformizing the surface charge and inhibiting the formation of lithium dendrites. Summary of the invention
[0004] In view of the above problems, the present invention provides a high-performance solid-state battery.
[0005] The present invention provides a high-performance solid-state battery containing a CPL-LCF composite lithium metal negative electrode material and a preparation method thereof, characterized in that the method comprises: step (1) preparing LLZTO powder, step (2) preparing LLZTO electrolyte sheet, step (3) preparing ZnI 2@ Preparation of LLZTO electrolyte sheet, step (4) preparation of LAGP powder, step (5) preparation of CPL composite layer lithium foil, step (6) Si / C composite negative electrode material, step (7) CaF 2 Preparation, step (8) preparation of Si / C-CPL-LCF composite lithium metal negative electrode, step (9) preparation of LFP composite positive electrode, step (10) preparation of battery assembly.
[0006] Among them, step (3) ZnI 2 The preparation of @LLZTO electrolyte sheet includes: A certain amount of ZnI 2 The powder was added to anhydrous ethanol to prepare a certain concentration of ZnI 2 solution, and place the bare LLZTO sheet prepared in step (2) on the ZnI 2 ZnI was prepared in solution 2 @LLZTO electrolyte tablets; Step (8) Preparation of Si / C-CPL-LCF composite lithium metal negative electrode comprises: The CPL composite layer lithium foil prepared in step (5) is placed in a stainless steel container and heated. The CaF 2 The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a certain mass ratio and continuously stirred to react with the molten lithium, and finally a CaLi 2 A composite lithium metal anode of alloy, LiF and Si / C, referred to as Si / C-CPL-LCF composite lithium metal anode; Preferably, step (1) preparation of LLZTO powder First, LiOH·H 2 O.La 2 O 3 、ZrO 2 、 2 O 5 and Al 2 O 3 The ball milling beads are zirconium oxide ball milling beads, and the solvent is isopropanol, wherein LiOH·H 2 O is excessive to compensate for the loss of lithium during high temperature calcination, Al 2 O 3 As a sintering aid, a planetary ball mill is used for ball milling at a certain speed and time. Subsequently, the ball liquid is placed in an oven, dried and sieved, and the ball-milled powder is calcined at a high temperature, heated at a certain rate, kept warm for a certain time, cooled, and finally, the product is continued to be ball milled for a certain time, dried and sieved to obtain LLZTO powder; Preferably, step (2) preparation of LLZTO sheet The LLZTO powder prepared in step (1) is pressed into a sheet, sintered at a certain temperature, and slowly cooled to obtain a dense LLZTO sheet. Next, the prepared LLZTO sheet is polished in sequence using sandpaper. Finally, the polished LLZTO sheet is stored in a glove box filled with argon gas. Preferably, step (3) ZnI 2 Preparation of LLZTO electrolyte sheets The LLZTO sheet prepared in step (2) is mixed with a certain amount of ZnI 2 The powder was added to anhydrous ethanol to prepare a certain concentration of ZnI 2 solution, the bare LLZTO sheet was placed on ZnI 2 ZnI was prepared in solution 2 @LLZTO electrolyte tablets; Preferably, step (4) preparation of LAGP powder LiOH·H was prepared by ball milling 2 O.A l2 O 3 ,GeO 2 and NH 4 H 2 PO 4 Mix completely according to the stoichiometric ratio and heat at a certain temperature for a certain time to make LiOH·H 2 O and NH 4 H 2 PO 4 After being fully decomposed, the above precursor is sintered to obtain a main phase of Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 The solid electrolyte powder is then ball-milled and sieved to obtain LAGP powder; Preferably, step (5) preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, using NMP (N-methylpyrrolidone) as a dispersant, the LAGP powder prepared in step (4) and PVDF (polyvinylidene fluoride) are mixed according to a weight ratio and magnetically stirred, and the slurry is applied to the surface of lithium foil by a drop coating method, and then dried under vacuum conditions to obtain a lithium foil with a CPL coating; Preferably, step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh silicon powder and graphite powder, prepare raw materials of a certain mass ratio, mix the weighed silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process, put the mixed raw materials into a ball tank, add an appropriate amount of agate balls into the ball mill, and at the same time, add anhydrous ethanol as a ball milling medium according to a certain material-liquid ratio to reduce the agglomeration of the raw materials. After the ball mill is sealed, put it into a planetary ball mill, set a certain speed and start the ball mill for ball milling to ensure that the raw materials are fully mixed and refined. Finally, put the ball-milled mixture into a vacuum drying oven for drying. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and use a sieve to screen it to obtain a Si / C composite negative electrode material; Preferably, in step (7), CaF 2 Preparation First, C 4 H 6 CaO was added to deionized water, and then C 6 H 5 Na 3 O 7 Then, add NaBF 4 The pH value of the solution was adjusted to a certain value with ammonia water, and the mixed solution was finally transferred to a polytetrafluoroethylene reactor for hydrothermal reaction, washing and drying to obtain CaF 2 Particles; Preferably, step (8) preparation of Si / C-CPL-LCF composite lithium metal negative electrode First, the CPL composite layer lithium foil prepared in step (5) is placed in a stainless steel container and heated, and the CaF prepared in step (7) is placed in a stainless steel container and heated. 2 The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a certain mass ratio and continuously stirred to react with the molten lithium, and finally a CaLi 2 A composite lithium metal anode of alloy, LiF and Si / C, referred to as Si / C-CPL-LCF composite lithium metal anode; Preferably, step (9) preparation of LFP composite positive electrode First, the active material, conductive agent CNT and CSSE@20 homogeneous solution are mixed according to the mass ratio, and N-methylpyrrolidone (NMP) is used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry is evenly coated on the aluminum current collector. Secondly, the coated pole piece is transferred to an oven for vacuum drying to remove ACN and NMP agents. Finally, after the pole piece is dried, the pole piece is cut into a circular pole piece by a punching machine, compacted, weighed, and vacuum dried again. The fully dried pole piece is transferred to a glove box for storage to obtain an LFP composite positive electrode; Preferably, step (10) preparation of battery assembly The positive and negative electrodes use the same electrode pieces such as Si / C-CPL-LCF and LFP. The Si / C-CPL-LCF and LFP electrodes are cut into round pieces by a puncher. The electrolyte is ZnI 2 @LLZTO, Finally, assemble the battery in an argon-filled glove box.
[0007] Preferably, step (1) preparation of LLZTO powder LLZTO powder was prepared by solid phase method. 74-75g LiOH·H 2 O, 116-117gLa 2 O 3 51-52gZrO 2 , 13-14gTa 2 O 5 and 3-4gAl 2 O 3 The ball milling beads are zirconium oxide ball milling beads, and the solvent is isopropanol, wherein LiOH·H 2 O is 10-20% excessive to compensate for the loss of lithium during high temperature calcination, Al 2 O 3 The powder is calcined at a high temperature, heated to 500-1000°C at a rate of 1-5°C / min, kept warm for 5-10 hours, cooled, and the product is ball milled for 36-48 hours, dried, and sieved to obtain LLZTO powder.
[0008] The present invention has the advantages that the surface physical and chemical properties of the LLZTO powder prepared by the solid phase method are stable, the surface chemical stability of the electrolyte material in contact with media such as air and water can be improved, and the redox side reaction at the interface between the electrolyte material and the positive and negative electrode materials of the lithium battery can be inhibited.
[0009] Preferably, step (2) preparation of LLZTO sheet The LLZTO powder prepared in step (1) is pressed into a sheet at 100-500 KPa, sintered at 500-1000° C. for 1-5 h, and slowly cooled at 1-5° C. / min to obtain a dense LLZTO sheet with a diameter of ≈10-15 mm and a thickness of ≈0-1 mm. Finally, the prepared LLZTO sheet is polished in sequence using 200-400 mesh, 600-800 mesh, 1300-1500 mesh and 2800-3000 mesh sandpaper to control the thickness to ≈0-1 mm. The polished LLZTO electrolyte sheet is stored in a glove box filled with argon.
[0010] The present invention has the advantages that, through precise control of pressure and sintering temperature, LLZTO sheets of specific size and thickness can be prepared, the polishing process can remove surface defects and impurities, improve the surface quality of the electrolyte sheet, and storage in a glove box filled with argon can prevent the surface of the LLZTO sheet from being oxidized or hygroscopic.
[0011] Preferably, step (3) ZnI 2 Preparation of LLZTO electrolyte sheets 0.1-1.5 g ZnI 2 The powder was added to anhydrous ethanol to prepare a certain concentration of ZnI 2 solution, the bare LLZTO sheet was placed on ZnI 2 The ZnI was prepared in the solution for 5-10 seconds. 2 @LLZTO electrolyte tablets.
[0012] The invention has the advantage that the LLZTO sheet can be quickly immersed in ZnI 2 In the solution, a uniform ZnI 2 Coating, ZnI 2 The coating can enhance the interfacial stability between LLZTO and lithium metal and reduce interfacial side reactions.
[0013] Step (4) Preparation of LAGP powder 1-2 mol LiOH·H was prepared by ball milling 2 O, 0-1 molAl 2 O 3 、2-3molGeO 2 and 2-3 molNH 4 H 2 PO 4 Mix thoroughly and heat at 500-1000℃ for 1-5h to make LiOH·H 2 O and NH 4 H 2 PO 4After being fully decomposed, the precursor is sintered at 500-1000℃ for 5-10h to obtain a Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 The solid electrolyte powder is ball-milled for 12-24 hours and passed through a 100-500 mesh sieve to obtain LAGP powder.
[0014] The present invention has the advantage that high-purity and uniform LAGP powder can be prepared by ball milling and high-temperature sintering, and the electrochemical performance of LAGP can be ensured by accurately controlling the stoichiometric ratio.
[0015] Preferably, step (5) preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, LAGP powder and PVDF are mixed in a weight ratio of 1:5-5:5 with NMP as a dispersant and magnetically stirred for 5-10 hours. The slurry is applied on the surface of lithium foil with a thickness of 100-450 μm by drop coating, and then dried under vacuum conditions at 30-50°C for 8-12 hours to obtain a lithium foil with a CPL coating.
[0016] The invention has the advantages that the CPL composite layer can enhance the interface stability between the lithium foil and the electrolyte, and the CPL layer can be used as a protective layer to reduce the direct contact between the lithium foil and the electrolyte, thereby improving the safety of the battery.
[0017] Preferably, step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and ensure that each group of raw materials is mixed evenly in a ratio of 1:9-4:6 to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into the ball tank, and add an appropriate amount of agate balls to the ball mill according to the ratio of ball to material of 1:1-5:1. At the same time, add anhydrous ethanol as the ball milling medium according to the material-liquid ratio of 1:1-1:5. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process, and at the same time reduce the agglomeration of raw materials. For example, after sealing the ball mill jar, put it into a planetary ball mill, set the speed to 100-500rpm and start the ball mill for ball milling. The ball milling time is 15-20h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 50-100℃. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 100-500 mesh sieve for sieving.
[0018] The advantages of the present invention are that the Si / C composite material has a high specific capacity, can significantly improve the energy density of the battery, and the composite of Si and C can effectively alleviate the volume expansion problem of silicon during the charging and discharging process.
[0019] Preferably, in step (7), CaF 2 Preparation First, 1-5mmolC 4 H 6 Add CaO to 50-100 mL of deionized water, then add 5-15 mmol C 6 H 5 Na 3 O 7 Stir evenly and add 1-5mmol NaBF to the solution. 4 The pH value of the solution was adjusted to 10-11 with ammonia water, and the mixed solution was transferred to a 50-100 mL polytetrafluoroethylene reactor, and hydrothermally reacted at 150-200 ° C for 0-1 h, and finally washed and dried to obtain CaF 2 Particles.
[0020] The present invention has the advantage that the hydrothermal method is a simple and efficient synthesis method and can prepare high-quality CaF 2 particles, by adjusting the reaction conditions, the CaF 2 Crystal growth.
[0021] Preferably, step (8) preparation of Si / C-CPL-LCF composite lithium metal negative electrode First, the CPL composite layer lithium foil prepared in step (5) is placed in a stainless steel container and heated to 100-500°C, and the CaF prepared in step (7) is placed in a stainless steel container and heated to 100-500°C. 2 The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a mass ratio of 20:1-25:1, and stirred continuously to react with the molten lithium, and finally a CaLi 2 Alloy and Si / C composite lithium metal anode.
[0022] The present invention has the advantages that the Si / C-CPL-LCF composite structure can improve the electrochemical performance and structural stability of the negative electrode material, and the CaLi 2 The addition of alloys can enhance the conductivity of negative electrode materials.
[0023] The third technical objective of the present invention is achieved through the following technical solutions: Preferably, step (9) preparation of LFP composite positive electrode First, the active material, conductive agent CNT and CSSE@20 homogeneous solution were mixed in a mass ratio of 5:10:10-80:20:20, and NMP was used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry was evenly coated on the aluminum current collector, and the coated pole piece was transferred to an oven and vacuum dried at 50-100°C for 8-12h to remove ACN and NMP agents. After the pole piece was dried, a punching machine was used to cut the pole piece into a circular pole piece with a diameter of 10-15mm. After compaction and weighing, it was vacuum dried again at 50-100°C for 8-12h. The pole piece after sufficient drying was transferred to a glove box for storage. The LFP composite positive electrode active material loading was about 0-1mg / cm 2 .
[0024] The advantages of the present invention are that the LFP positive electrode material has a high specific capacity and good cycle stability, and the performance of the positive electrode can be optimized by adjusting the ratio of the active material, the conductive agent and the binder in the slurry.
[0025] Preferably, step (10) preparation of battery assembly The same electrode was used for both the positive and negative electrodes. The Si / C-CPL-LCF prepared in step (8) and the LFP prepared in step (9) were cut into discs with a diameter of 10-15 mm using a puncher. The ZnI prepared in step (3) was used as the electrolyte. 2 @LLZTO, Finally, the battery was assembled in an argon-filled glove box (water oxygen content less than 0-1ppm).
[0026] The advantages of the present invention are that the consistency and reliability of battery assembly can be ensured by precisely controlling the size and shape of the pole pieces, and assembling the battery in a glove box filled with argon gas can prevent the battery materials from being oxidized or absorbing moisture during the assembly process, thereby improving the safety and performance of the battery.
[0027] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantages that the surface physical and chemical properties of the LLZTO powder prepared by the solid phase method are stable, which can improve the surface chemical stability of the electrolyte material in contact with media such as air and water, and inhibit the redox side reaction at the interface between the electrolyte material and the positive and negative electrode materials of the lithium battery; 2. The present invention has the advantages that, through precise control of pressure and sintering temperature, LLZTO sheets of specific size and thickness can be prepared, the polishing process can remove surface defects and impurities, improve the surface quality of the electrolyte sheet, and storage in a glove box filled with argon can prevent the surface of the LLZTO sheet from oxidation or moisture absorption; 3. The advantage of the present invention is that the LLZTO sheet can be quickly immersed in ZnI 2In the solution, a uniform ZnI 2 Coating, ZnI 2 The coating can enhance the interfacial stability between LLZTO and lithium metal and reduce interfacial side reactions; 4. The present invention has the advantage that high-purity and uniform LAGP powder can be prepared by ball milling and high-temperature sintering, and the electrochemical performance of LAGP can be ensured by accurately controlling the stoichiometric ratio; 5. The present invention has the advantage that the CPL composite layer can enhance the interface stability between the lithium foil and the electrolyte, and the CPL layer can serve as a protective layer to reduce the direct contact between the lithium foil and the electrolyte, thereby improving the safety of the battery; 6. The advantages of the present invention are that the Si / C composite material has a high specific capacity, which can significantly improve the energy density of the battery, and the composite of Si and C can effectively alleviate the volume expansion problem of silicon during the charging and discharging process; 7. The advantage of the present invention is that the hydrothermal method is a simple and efficient synthesis method that can prepare high-quality CaF 2 particles, by adjusting the reaction conditions, the CaF 2 Growth of crystals; 8. The advantages of the present invention are that the Si / C-CPL-LCF composite structure can improve the electrochemical performance and structural stability of the negative electrode material, CaLi 2 The addition of alloys can enhance the conductivity of negative electrode materials; 9. The advantages of the present invention are that the LFP positive electrode material has a high specific capacity and good cycle stability, and the performance of the positive electrode can be optimized by adjusting the ratio of the active material, the conductive agent and the binder in the slurry; 10. The advantage of adopting the present invention is that the consistency and reliability of battery assembly can be ensured by precisely controlling the size and shape of the electrode pieces. Assembling the battery in a glove box filled with argon gas can prevent the battery materials from being oxidized or absorbing moisture during the assembly process, thereby improving the safety and performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a high-performance solid-state battery containing CPL-LCF composite lithium metal negative electrode material and a flow chart of its preparation method.
[0029] Figure 2 It is a battery structure diagram. DETAILED DESCRIPTION
[0030] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0031] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.
[0032] Example 1
[0033] Step (1) Preparation of LLZTO powder LLZTO powder was prepared by solid phase method. 74-gLiOH·H 2 O、116gLa 2 O 3 、51gZrO 2 ,13gTa 2 O 5 and 3gAl 2 O 3 The ball milling beads are zirconium oxide ball milling beads, and the solvent is isopropanol, wherein LiOH·H 2 O is 10% excess to compensate for the loss of lithium during high temperature calcination, Al 2 O 3 As a sintering aid, a planetary ball mill was used for ball milling at a speed of 100r / min for 10h, and then the ball liquid was placed in an oven at 50℃ for 36h and sieved after drying. The ball-milled powder was calcined at high temperature, heated to 500℃ at a rate of 1℃ / min, kept warm for 5h, cooled, and the product was ball milled for 36h, dried and sieved to obtain LLZTO powder. Step (2) Preparation of LLZTO Sheet The LLZTO powder prepared in step (1) is pressed into a sheet at 100 KPa, sintered at 500 ° C for 1 h, and slowly cooled at 1 ° C / min to obtain a dense LLZTO sheet with a diameter of ≈10 mm and a thickness of ≈1 mm. Finally, the prepared LLZTO sheet is polished in sequence using 200 mesh, 600 mesh, 1300 mesh and 2800 mesh sandpaper to control the thickness to ≈1 mm. The polished LLZTO electrolyte sheet is stored in a glove box filled with argon; Step (3) ZnI 2 Preparation of LLZTO electrolyte sheets 0.1 g ZnI 2 The powder was added to anhydrous ethanol to prepare a certain concentration of ZnI 2 solution, the bare LLZTO sheet was placed on ZnI 2 ZnI was prepared in solution for 5 seconds 2 @LLZTO electrolyte tablets; Step (4) Preparation of LAGP powder First, 1 mol LiOH·H 2O, 0.2 molAl 2 O 3 2molGeO 2 and 2 molNH 4 H 2 PO 4 Mix thoroughly and heat at 500 °C for 1 h to make LiOH·H 2 O and NH 4 H 2 PO 4 After being fully decomposed, the precursor was sintered at 500 °C for 5 h to obtain a Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 The solid electrolyte powder was ball-milled for 12 h and passed through a 100-mesh sieve to obtain LAGP powder; Step (5) Preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, LAGP powder and PVDF were mixed in a weight ratio of 1:5 with NMP as a dispersant and magnetically stirred for 5 h, and the slurry was applied on the surface of lithium foil with a thickness of 100 μm by drop coating, and then dried under vacuum at 30 ° C for 8 h to obtain a lithium foil with a CPL coating; Step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and ensure that each group of raw materials is in a ratio of 1:9. Mix the weighed silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into a ball tank, and add an appropriate amount of agate balls to the ball mill according to a ball-to-material ratio of 1:1. At the same time, add anhydrous ethanol as a ball milling medium according to a material-liquid ratio of 1:1. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process and reduce the agglomeration of raw materials. After the ball mill is sealed, put it into a planetary ball mill, set the speed to 100rpm and start the ball mill for ball milling. The ball milling time is 15h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 50°C. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 100-mesh sieve for sieving; Step (7) CaF 2 Preparation First, 1mmolC 4 H 6 CaO was added to 50 mL of deionized water, followed by 5 mmol of C 6 H 5 Na 3 O7 Stir well and add 1mmolNaBF 4 The pH value of the solution was adjusted to 11 with ammonia water, and the mixed solution was transferred to a 50 mL polytetrafluoroethylene reactor for hydrothermal reaction at 150 ° C for 0.2 h. Finally, CaF 2 Particles; Step (8) Preparation of Si / C-CPL-LCF composite lithium metal anode The CPL composite lithium foil prepared in step (5) was placed in a stainless steel container and heated to 100°C. The CaF 2 The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a mass ratio of 20:1, and stirred continuously to react with the molten lithium, and finally a CaLi 2 Alloy and Si / C composite lithium metal anode; Step (9) Preparation of LFP composite positive electrode First, the active material, conductive agent CNT and CSSE@20 homogeneous solution were mixed in a mass ratio of 50:10:10, and NMP was used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry was evenly coated on the aluminum current collector, and the coated electrode was transferred to an oven and vacuum dried at 50°C for 8 hours to remove ACN and NMP agents. After the electrode was dried, a punching machine was used to cut the electrode into a circular electrode with a diameter of 10 mm. After compaction and weighing, it was vacuum dried again at 50°C for 8 hours. The fully dried electrode was transferred to a glove box for storage. The LFP composite positive electrode active material loading was about 0.2 mg / cm 2 ; Step (10) Preparation of battery assembly First, the same electrode was used for both the positive and negative electrodes. The Si / C-CPL-LCF prepared in step (8) and the LFP prepared in step (9) were cut into discs with a diameter of 10 mm using a punch. Secondly, the electrolyte was the ZnI prepared in step (3). 2 @LLZTO, finally, the battery was assembled in an argon-filled glove box (water oxygen content less than 0.1 ppm).
[0034] Example 2
[0035] Step (1) Preparation of LLZTO powder LLZTO powder was prepared by solid phase method. 74.5 g LiOH·H 2 O, 116.5gLa 2 O 3 ,51.5gZrO 2 , 13.5gTa2 O 5 and 3.5gAl 2 O 3 The ball milling beads are zirconium oxide ball milling beads, and the solvent is isopropanol, wherein LiOH·H 2 O is 15% excess to compensate for the loss of lithium during high temperature calcination, Al 2 O 3 As a sintering aid, a planetary ball mill was used for ball milling at a speed of 200r / min for 12h, and then the ball liquid was placed in an oven at 70℃ for 40h and sieved after drying. The ball-milled powder was calcined at high temperature, heated to 700℃ at a rate of 2℃ / min, kept warm for 8h, cooled, and the product was ball milled for 40h, dried and sieved to obtain LLZTO powder; Step (2) Preparation of LLZTO Sheet The LLZTO powder prepared in step (1) was pressed into a sheet at 200 KPa, sintered at 700 ° C for 2 h, and slowly cooled at 2 ° C / min to obtain a dense LLZTO sheet with a diameter of ≈12 mm and a thickness of ≈0.2 mm. Finally, the prepared LLZTO sheet was polished in sequence using 300 mesh, 700 mesh, 1400 mesh and 2900 mesh sandpaper to control the thickness to ≈0.2 mm. The polished LLZTO electrolyte sheet was stored in a glove box filled with argon; Step (3) ZnI 2 Preparation of LLZTO electrolyte sheets 0.5 g ZnI 2 The powder was added to anhydrous ethanol to prepare a certain concentration of ZnI 2 solution, the bare LLZTO sheet was placed on ZnI 2 Preparation of ZnI in solution in 7s 2 @LLZTO electrolyte tablets; Step (4) Preparation of LAGP powder First, 1.5 mol LiOH·H 2 O, 0.5 molAl 2 O 3 , 2.5molGeO 2 and 2.5 molNH 4 H 2 PO 4 Mix thoroughly and heat at 700 °C for 2 h to make LiOH·H 2 O and NH 4 H 2 PO 4 After being fully decomposed, the precursor was sintered at 700 °C for 7 h to obtain a Li 1.5 Al 0.5 Ge 1.5(PO 4 ) 3 The solid electrolyte powder was ball-milled for 14 h and passed through a 200-mesh sieve to obtain LAGP powder; Step (5) Preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, LAGP powder and PVDF were mixed in a weight ratio of 3:5 with NMP as a dispersant and magnetically stirred for 7 hours, and the slurry was applied on the surface of lithium foil with a thickness of 250 μm by drop coating, and then dried under vacuum at 40°C for 10 hours to obtain a lithium foil with a CPL coating; Step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and ensure that each group of raw materials is in a ratio of 2:7. Mix the weighed silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into a ball tank, and add an appropriate amount of agate balls to the ball mill according to a ball-to-material ratio of 3:1. At the same time, add anhydrous ethanol as a ball milling medium according to a material-liquid ratio of 1:3. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process and reduce the agglomeration of raw materials. After the ball mill is sealed, put it into a planetary ball mill, set the speed to 200rpm and start the ball mill for ball milling. The ball milling time is 17h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 70°C. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 500-mesh sieve for sieving; Step (7) CaF 2 Preparation First, 2mmolC 4 H 6 CaO was added to 70 mL of deionized water, followed by 10 mmol of C 6 H 5 Na 3 O 7 Stir well and add 2mmolNaBF 4 The pH value of the solution was adjusted to 10.5 with ammonia water, and the mixed solution was transferred to a 75 mL polytetrafluoroethylene reactor for hydrothermal reaction at 175 ° C for 0.2 h. Finally, CaF 2 Particles; Step (8) Preparation of Si / C-CPL-LCF composite lithium metal anode The CPL composite layer lithium foil prepared in step (5) is placed in a stainless steel container and heated to 200°C. The CaF 2The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a mass ratio of 22.5:1, and stirred continuously to react with the molten lithium, and finally a CaLi 2 Alloy and Si / C composite lithium metal anode; Step (9) Preparation of LFP composite positive electrode The active material, conductive agent CNT and CSSE@20 homogeneous solution were mixed in a mass ratio of 65:15:15, and NMP was used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry was evenly coated on the aluminum current collector, and the coated electrode was transferred to an oven and vacuum dried at 75°C for 10 hours to remove ACN and NMP agents. After the electrode was dried, a punching machine was used to cut the electrode into a circular electrode with a diameter of 12 mm. After compaction and weighing, it was vacuum dried again at 75°C for 10 hours. The fully dried electrode was transferred to a glove box for storage. The LFP composite positive electrode active material loading was about 0.5 mg / cm 2 ; Step (10) Preparation of battery assembly First, the same electrode was used for both the positive and negative electrodes. The Si / C-CPL-LCF prepared in step (8) and the LFP prepared in step (9) were cut into discs with a diameter of 12 mm using a puncher. The ZnI prepared in step (3) was used as the electrolyte. 2 @LLZTO, the battery was assembled in an argon-filled glove box (water oxygen content less than 0.5 ppm).
[0036] Example 3
[0037] Step (1) Preparation of LLZTO powder LLZTO powder was prepared by solid phase method. 75 g LiOH·H 2 O、117gLa 2 O 3 52gZrO 2 ,14gTa 2 O 5 and 4gAl 2 O 3 The ball milling beads are zirconium oxide ball milling beads, and the solvent is isopropanol, wherein LiOH·H 2 O is 20% excess to compensate for the loss of lithium during high temperature calcination, Al 2 O 3As a sintering aid, a planetary ball mill was used for ball milling at a speed of 500r / min for 15h, and then the ball liquid was placed in an oven at 100℃ for 48h, sieved after drying, and the ball-milled powder was calcined at high temperature, heated to 1000℃ at a rate of 5℃ / min, kept warm for 10h, cooled, and the product was ball milled for 48h, dried and sieved to obtain LLZTO powder; Step (2) Preparation of LLZTO Sheet The LLZTO powder prepared in step (1) was pressed into a sheet at 500 KPa, sintered at 1000 ° C for 5 h, and slowly cooled at 5 ° C / min to obtain a dense LLZTO sheet with a diameter of ≈15 mm and a thickness of ≈1 mm. Finally, the prepared LLZTO sheet was polished in sequence using 400 mesh, 800 mesh, 1500 mesh and 3000 mesh sandpaper to control the thickness to ≈1 mm. The polished LLZTO electrolyte sheet was stored in a glove box filled with argon gas. Step (3) ZnI 2 Preparation of LLZTO electrolyte sheets 1.5 g ZnI 2 The powder was added to anhydrous ethanol to prepare ZnI 2 solution, the bare LLZTO sheet was placed on ZnI 2 ZnI was prepared in solution for 10s 2 @LLZTO electrolyte tablets; Step (4) Preparation of LAGP powder First, 2 mol LiOH·H 2 O, 1 molAl 2 O 3 3molGeO 2 and 3 molNH 4 H 2 PO 4 After complete mixing and heating at 1000℃ for 5h, LiOH·H 2 O and NH 4 H 2 PO 4 After being fully decomposed, the precursor was sintered at 1000 °C for 10 h to obtain a Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 The solid electrolyte powder was ball-milled for 24 h and passed through a 500-mesh sieve to obtain LAGP powder; Step (5) Preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, LAGP powder and PVDF were mixed in a weight ratio of 5:5 with NMP as a dispersant and magnetically stirred for 10 hours, and the slurry was applied on the surface of lithium foil with a thickness of 450 μm by drop coating, and then dried under vacuum at 50°C for 12 hours to obtain a lithium foil with a CPL coating; Step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and ensure that each group of raw materials is in a ratio of 4:6. Mix the weighed silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into a ball tank, and add an appropriate amount of agate balls to the ball mill according to a ball-to-material ratio of 5:1. At the same time, add anhydrous ethanol as a ball milling medium according to a material-liquid ratio of 1:5. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process and reduce the agglomeration of raw materials. After the ball mill is sealed, put it into a planetary ball mill, set the speed to 500rpm and start the ball mill for ball milling. The ball milling time is 20h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 100°C. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 500-mesh sieve for sieving; Step (7) CaF 2 Preparation First, 5mmolC 4 H 6 CaO was added to 100 mL of deionized water, followed by 15 mmol of C 6 H 5 Na 3 O 7 Stir well and add 5mmolNaBF 4 The pH value of the solution was adjusted to 11 with ammonia water, and the mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor for hydrothermal reaction at 200 °C for 1 h. Finally, CaF 2 Particles; Step (8) Preparation of Si / C-CPL-LCF composite lithium metal anode First, the CPL composite layer lithium foil prepared in step (5) was placed in a stainless steel container and heated to 500°C. The CaF 2 The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a mass ratio of 25:1, and stirred continuously to react with the molten lithium, and finally a CaLi 2 Alloy and Si / C composite lithium metal anode; Step (9) Preparation of LFP composite positive electrode First, the active material, conductive agent CNT and CSSE@20 homogeneous solution were mixed in a mass ratio of 80:20:20, and NMP was used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry was evenly coated on the aluminum current collector, and the coated electrode was transferred to an oven and vacuum dried at 100°C for 12 hours to remove ACN and NMP agents. After the electrode was dried, a punching machine was used to cut the electrode into a circular electrode with a diameter of 15 mm. After compaction and weighing, it was vacuum dried again at 100°C for 12 hours. The fully dried electrode was transferred to a glove box for storage. The LFP composite positive electrode active material loading was about 1 mg / cm 2 ; Step (10) Preparation of battery assembly First, the same electrode was used for both the positive and negative electrodes. The Si / C-CPL-LCF prepared in step (8) and the LFP prepared in step (9) were cut into discs with a diameter of 15 mm using a puncher. The ZnI prepared in step (3) was used as the electrolyte. 2 @LLZTO, finally, the battery was assembled in an argon-filled glove box (water oxygen content less than 1ppm).
[0038] Example 4
[0039] (1) Preparation of LLZTO powder LLZTO powder was prepared by solid phase method. 74.2 g LiOH·H 2 O, 116.4gLa 2 O 3 、51.3gZrO 2 , 13.1gTa 2 O 5 and 3.8gAl 2 O 3 The ball milling beads are zirconium oxide ball milling beads, and the solvent is isopropanol, wherein LiOH·H 2 O is 10% excess to compensate for the loss of lithium during high temperature calcination, Al 2 O 3 The ball mill was used as a sintering aid, with a planetary ball mill at a speed of 300 rmin for 12 h, and then the ball liquid was placed in an oven at 80 °C for 48 h, and sieved after drying. The ball-milled powder was calcined at high temperature, heated to 900 °C at a rate of 1 °C min, kept warm for 6 h, cooled, and the product was ball milled for 48 h, dried and sieved to obtain LLZTO powder; Step (2) Preparation of LLZTO Sheet The LLZTO powder prepared in step (1) was pressed into a sheet at 200 KPa, sintered at 1000° C. for 2 h, and slowly cooled at 3° C. / min to obtain a dense LLZTO sheet with a diameter of ≈15 mm and a thickness of ≈1 mm. Finally, the prepared LLZTO sheet was polished in sequence using 400 mesh, 800 mesh, 1500 mesh, and 3000 mesh sandpapers to control the thickness to ≈1.0 mm. The polished LLZTO electrolyte sheet was stored in a glove box filled with argon gas. Step (3) ZnI 2 Preparation of LLZTO electrolyte sheets 0.5 g ZnI 2 The powder was added to anhydrous ethanol to prepare a certain concentration of ZnI 2 solution, the bare LLZTO sheet was placed on ZnI 2 ZnI was prepared in solution for 10s 2 @LLZTO electrolyte tablets; Step (4) Preparation of LAGP powder 1.5 mol LiOH·H was prepared by ball milling 2 O, 0.5 molAl 2 O 3 , 2.5molGeO 2 and 3 molNH 4 H 2 PO 4 Mix thoroughly and heat at 700 °C for 4 h to make LiOH·H 2 O and NH 4 H 2 PO 4 After being fully decomposed, the precursor was sintered at 800 °C for 6 h to obtain a Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 The solid electrolyte powder was ball-milled for 24 h and passed through a 200-mesh sieve to obtain LAGP powder; Step (5) Preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, LAGP powder and PVDF were mixed in a weight ratio of 5:2 with NMP as a dispersant and magnetically stirred for 6 hours, and the slurry was applied on the surface of lithium foil with a thickness of 450 μm by drop coating, and then dried under vacuum at 40°C for 12 hours to obtain a lithium foil with a CPL coating; Step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and ensure that each group of raw materials is in a ratio of 3:7. Mix the weighed silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into a ball tank, and add an appropriate amount of agate balls to the ball mill according to a ball-to-material ratio of 5:1. At the same time, add anhydrous ethanol as a ball milling medium according to a material-liquid ratio of 1:4. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process and reduce the agglomeration of raw materials. After the ball mill is sealed, put it into a planetary ball mill, set the speed to 400rpm and start the ball mill for ball milling. The ball milling time is 16h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 90°C. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 400-mesh sieve for sieving; Step (7) CaF 2 Preparation First, 2mmolC 4 H 6 CaO was added to 60 mL of deionized water, followed by 10 mmol of C 6 H 5 Na 3 O 7 Stir well and add 4mmolNaBF 4 The pH value of the solution was adjusted to 10 with ammonia water, and the mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor for hydrothermal reaction at 150 ° C for 1 h. Finally, CaF 2 Particles; Step (8) Preparation of Si / C-CPL-LCF composite lithium metal anode The CPL composite lithium foil prepared in step (5) is placed in a stainless steel container and heated to 300°C. The CaF 2 The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a mass ratio of 25:1, and stirred continuously to react with the molten lithium, and finally a CaLi 2 Alloy and Si / C composite lithium metal anode; Step (9) Preparation of LFP composite positive electrode The active material, conductive agent CNT and CSSE@20 homogeneous solution were mixed in a mass ratio of 70:15:15, and NMP was used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry was evenly coated on the aluminum current collector, and the coated electrode was transferred to an oven and vacuum dried at 80°C for 10 hours to remove ACN and NMP agents. After the electrode was dried, a punching machine was used to cut the electrode into a circular electrode with a diameter of 14 mm. After compaction and weighing, it was vacuum dried again at 80°C for 10 hours. The fully dried electrode was transferred to a glove box for storage. The LFP composite positive electrode active material loading was about 0.5 mg / cm 2 ; Step (10) Preparation of battery assembly The positive and negative electrodes are made of the same electrode such as Si / C-CPL-LCF and LFP. The Si / C-CPL-LCF and LFP electrodes are cut into discs with a diameter of 13 mm using a puncher. Secondly, the electrolyte is ZnI 2 @LLZTO, finally, the battery was assembled in an argon-filled glove box (water oxygen content less than 0.1 ppm).
[0040] Comparative Example 1
[0041] Step (1) Preparation of LLZTO powder LLZTO powder was prepared by solid phase method. 75 g LiOH·H 2 O、117gLa 2 O 3 52gZrO 2 ,14gTa 2 O 5 and 4gAl 2 O 3 The ball milling beads are zirconium oxide ball milling beads, and the solvent is isopropanol, wherein LiOH·H 2 O is 20% excess to compensate for the loss of lithium during high temperature calcination, Al 2 O 3 As a sintering aid, a planetary ball mill was used for ball milling at a speed of 500r / min for 15h, and then the ball liquid was placed in an oven at 100℃ for 48h, sieved after drying, and the ball-milled powder was calcined at high temperature, heated to 1000℃ at a rate of 5℃ / min, kept warm for 10h, cooled, and the product was ball milled for 48h, dried and sieved to obtain LLZTO powder; Step (2) Preparation of LLZTO Sheet The LLZTO powder prepared in step (1) was pressed into a sheet at 500 KPa, sintered at 1000 ° C for 5 h, and slowly cooled at 5 ° C / min to obtain a dense LLZTO sheet with a diameter of ≈15 mm and a thickness of ≈1 mm. Finally, the prepared LLZTO sheet was polished in sequence using 400 mesh, 800 mesh, 1500 mesh and 3000 mesh sandpaper to control the thickness to ≈1 mm. The polished LLZTO electrolyte sheet was stored in a glove box filled with argon gas. Step (3) ZnI 2 Preparation of LLZTO electrolyte sheets 1.5 g ZnI 2 The powder was added to anhydrous ethanol to prepare a certain concentration of ZnI 2 solution, the bare LLZTO sheet was placed on ZnI 2 ZnI was prepared in solution for 10s 2 @LLZTO electrolyte tablets; Step (4) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and ensure that each group of raw materials is in a ratio of 4:6. Mix the weighed silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into a ball tank, and add an appropriate amount of agate balls to the ball mill according to a ball-to-material ratio of 5:1. At the same time, add anhydrous ethanol as a ball milling medium according to a material-liquid ratio of 1:5. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process and reduce the agglomeration of raw materials. After the ball mill is sealed, put it into a planetary ball mill, set the speed to 500rpm and start the ball mill for ball milling. The ball milling time is 20h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 100°C. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 500-mesh sieve for sieving; Step (5) CaF 2 Preparation 5mmolC 4 H 6 CaO was added to 100 mL of deionized water, followed by 15 mmol of C 6 H 5 Na 3 O 7 Stir well and add 5mmolNaBF 4 The pH value of the solution was adjusted to 11 with ammonia water, and the mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor for hydrothermal reaction at 200 °C for 1 h. Finally, CaF 2 Particles; Step (6) Preparation of Si / C-CPL-LCF composite lithium metal anode Place the lithium foil in a stainless steel container and heat it to 500°C. 2 The nanopowder and the Si / C composite negative electrode material prepared in step (4) are added to the molten lithium in a mass ratio of 25:1, and stirred continuously to react with the molten lithium, and finally a CaLi 2 Alloy and Si / C composite lithium metal anode; Step (7) Preparation of LFP composite positive electrode The active material, conductive agent CNT and CSSE@20 homogeneous solution were mixed in a mass ratio of 80:20:20, and NMP was used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry was evenly coated on the aluminum current collector, and the coated electrode was transferred to an oven and vacuum dried at 100°C for 12 hours to remove ACN and NMP agents. After the electrode was dried, a punching machine was used to cut the electrode into a circular electrode with a diameter of 15 mm. After compaction and weighing, it was vacuum dried again at 100°C for 12 hours. The fully dried electrode was transferred to a glove box for storage. The LFP composite positive electrode active material loading was about 1 mg / cm 2 ; Step (8) Preparation of battery assembly The same electrode was used for both the positive and negative electrodes. The Si / C-CPL-LCF prepared in step (6) and the LFP prepared in step (7) were cut into discs with a diameter of 15 mm using a puncher. The electrolyte was the ZnI prepared in step (3). 2 @LLZTO, the battery was assembled in an argon-filled glove box (water oxygen content less than 1ppm).
[0042] Comparative Example 2
[0043] Step (1) Preparation of LAGP powder 2 molLiOH·H was prepared by ball milling 2 O, 1 molAl 2 O 3 3molGeO 2 and 3 molNH 4 H 2 PO 4 After complete mixing and heating at 1000℃ for 5h, LiOH·H 2 O and NH 4 H 2 PO 4 After being fully decomposed, the precursor was sintered at 1000 °C for 10 h to obtain a Li 1.5 Al 0.5Ge 1.5 (PO 4 ) 3 The solid electrolyte powder was ball-milled for 24 h and passed through a 500-mesh sieve to obtain LAGP powder; Step (2) Preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, LAGP powder and PVDF were mixed in a weight ratio of 5:5 with NMP as a dispersant and magnetically stirred for 10 hours, and the slurry was applied on the surface of lithium foil with a thickness of 450 μm by drop coating, and then dried under vacuum at 50°C for 12 hours to obtain a lithium foil with a CPL coating; Step (3) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and ensure that each group of raw materials is in a ratio of 4:6. Mix the silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into a ball tank, and add an appropriate amount of agate balls to the ball mill according to a ball-to-material ratio of 5:1. At the same time, add anhydrous ethanol as a ball milling medium according to a material-liquid ratio of 1:5. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process and reduce the agglomeration of raw materials. After the ball mill is sealed, put it into a planetary ball mill, set the speed to 500rpm and start the ball mill for ball milling. The ball milling time is 20h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 100°C. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 500-mesh sieve for sieving; Step (4) CaF 2 Preparation 5mmolC 4 H 6 CaO was added to 100 mL of deionized water, followed by 15 mmol of C 6 H 5 Na 3 O 7 Stir well and add 5mmolNaBF 4 The pH value of the solution was adjusted to 11 with ammonia water, and the mixed solution was transferred to a 100 mL polytetrafluoroethylene reactor for hydrothermal reaction at 200 °C for 1 h. Finally, CaF 2 Particles; Step (5) Preparation of Si / C-CPL-LCF composite lithium metal anode Place the lithium foil in a stainless steel container and heat it to 500°C. 2The nanopowder and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a mass ratio of 25:1, and stirred continuously to react with the molten lithium, and finally a CaLi 2 Alloy and Si / C composite lithium metal anode; Step (6) Preparation of LFP composite positive electrode The active material, conductive agent CNT and CSSE@20 homogeneous solution were mixed in a mass ratio of 80:20:20, and NMP was used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry was evenly coated on the aluminum current collector, and the coated electrode was transferred to an oven and vacuum dried at 100°C for 12 hours to remove ACN and NMP agents. After the electrode was dried, a punching machine was used to cut the electrode into a circular electrode with a diameter of 15 mm. After compaction and weighing, it was vacuum dried again at 100°C for 12 hours. The fully dried electrode was transferred to a glove box for storage. The LFP composite positive electrode active material loading was about 1 mg / cm 2 ; Step (7) Preparation of battery assembly The same electrode pieces were used for both the positive and negative electrodes. The Si / C-CPL-LCF prepared in step (8) and the LFP prepared in step (3) were cut into discs with a diameter of 15 mm using a puncher. Then, electrolyte was used. Finally, the battery was assembled in a glove box filled with argon (water and oxygen content less than 1 ppm).
[0044] Inspection test comparison:
[0045] The high-performance solid-state batteries containing CPL-LCF composite lithium metal negative electrode materials obtained in Examples 1 to 4 and comparative examples 1 and 2 were tested. The specific testing methods are as follows: Electrochemical stability test The electrochemical stability of the electrolyte was tested by linear sweep voltammetry (LSV) combined with cyclic voltammetry (CV). The working electrodes included a stainless steel (ss) electrode, a conductive agent CNT electrode and an aluminum (Al) electrode. The metal lithium electrode was used as the counter electrode and the reference electrode. The test system was encapsulated in a button battery case in a glove box, and then the sealed test battery was taken out for heat treatment (80°C, 1h). The electrochemical stability of different electrolyte systems was tested under constant temperature conditions (30°C, 35°C, 60°C) with a scan rate of 0.5mV / s.
[0046] Conductivity meter test The room temperature ionic conductivity of different liquid and plastic crystalline SN-based electrolytes was tested using a conductivity meter. Before the conductivity test, the conductivity meter was first calibrated with a KCl solution with a concentration of 1 mol / L, and then the ionic conductivity test of the electrolyte system was performed. In order to ensure the accuracy of the test, the plastic crystalline electrolyte was first heated and melted to ensure the interface contact of the electrodes, and then cooled to room temperature for testing.
[0047] AC impedance test Electrochemical impedance spectroscopy (EIS) is widely used to detect the physical and chemical processes of lithium-ion batteries. In a typical EIS experiment, a small sinusoidal perturbation voltage E(t) is first applied to an electrochemical system, and the ratio of the linear current density j(t) to the input voltage E(t) is the impedance Z(t). This experiment is called a constant potential EIS test (PEIS). When the input current is alternating current, the experiment is called a constant current EIS test (GEIS).
[0048] Table 1 Electrochemical stability test
[0049] As can be seen from Table 1, Example 4 is the best, while Comparative Example 2 is relatively poor. The data of the comparative example is obviously larger than that of the example, indicating that the addition of the solid electrolyte ZnI 2 @LLZTO shows good electrochemical stability. 2 The reaction can form an air-stable layer on the surface of LLZTO, which helps to improve its contact with lithium metal and reduce the interface resistance. The addition of LLZTO reduces the crystallinity of the PEO-based electrolyte, improves the ionic conductivity, electrochemical stability window and lithium ion migration number, and improves the chemical stability of the electrolyte with metallic lithium.
[0050] Table 2 Conductivity meter test
[0051] As can be seen from Table 2, Example 4 is the best, while Comparative Example 2 is relatively poor. The comparative data is significantly larger than that of the example, indicating that the Si / C-CPL-LCF composite lithium metal negative electrode material plays a certain role in ionic conductivity. In the Si / C composite negative electrode material, the carbon material acts as a conductive network to improve the conductivity of the composite material, providing a good contact medium during the charge and discharge process. During the lithium ion transmission process, the carbon material can improve the transmission of lithium ions between the active material and the interface. The coating can improve the morphology of the surface of the silicon oxide negative electrode material, thereby improving the Li + The transport at the active material / electrolyte interface improves the rate performance.
[0052] Table 3 AC impedance test
[0053] As can be seen from Table 3, Example 4 is the best and Comparative Example 2 is relatively poor. The comparative example data is significantly larger than that of the embodiment, indicating that the high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material has good performance in the AC impedance test. By using the CPL-LCF composite lithium metal negative electrode, the interfacial impedance of the battery can be reduced. During the long cycle process, the battery using the CPL-LCF composite lithium metal negative electrode exhibits good interface stability, and the polarization does not increase significantly with the progress of the cycle, indicating good interface stability and low impedance increase.
[0054] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A high-performance solid-state battery containing a CPL-LCF composite lithium metal negative electrode material and a preparation method thereof, characterized in that: include: Step (1) preparation of LLZTO powder, step (2) preparation of LLZTO electrolyte sheet, step (3) preparation of ZnI2@LLZTO electrolyte sheet, step (4) preparation of LAGP powder, step (5) preparation of CPL composite layer lithium foil, step (6) preparation of Si / C composite negative electrode material, step (7) preparation of CaF2, step (8) preparation of Si / C-CPL-LCF composite lithium metal negative electrode, step (9) preparation of LFP composite positive electrode, step (10) preparation of battery assembly; Wherein, the preparation of the ZnI2@LLZTO electrolyte sheet in step (3) comprises: A certain amount of ZnI2 powder is added into anhydrous ethanol to prepare a ZnI2 solution of a certain concentration, and the LLZTO sheet prepared in step (2) is placed into the ZnI2 solution to prepare a ZnI2@LLZTO electrolyte sheet; Step (8) Preparation of Si / C-CPL-LCF composite lithium metal negative electrode comprises: The CPL composite layer lithium foil prepared in step (5) is placed in a stainless steel container and heated, and the CaF2 nanopowder prepared in step (7) and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a certain mass ratio, and are continuously stirred to react with the molten lithium, and finally a composite lithium metal negative electrode containing CaLi2 alloy, LiF and Si / C is obtained, which is referred to as Si / C-CPL-LCF composite lithium metal negative electrode.
2. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 1, characterized in that: Step (1) Preparation of LLZTO powder First, LiOH·H2O, La2O3, ZrO2, Ta2O5 and Al2O3 are added to a ball mill in sequence, zirconia ball mills are used as ball milling beads, isopropanol is used as solvent, LiOH·H2O is excessive to compensate for the loss of lithium during high-temperature calcination, Al2O3 is used as a sintering aid, a planetary ball mill is used for ball milling at a certain speed and time, then the ball liquid is put into an oven, dried and sieved, the ball milled powder is calcined at a high temperature, heated at a certain rate, kept warm for a certain time, cooled, and finally, the product is continued to be ball milled for a certain time, dried and sieved to obtain LLZTO powder; Step (2) Preparation of LLZTO electrolyte sheet The LLZTO powder prepared in step (1) is pressed into a sheet, sintered at a certain temperature, and slowly cooled to obtain a dense LLZTO sheet. Next, the prepared LLZTO sheet is polished in sequence using sandpaper. Finally, the polished LLZTO electrolyte sheet is stored in a glove box filled with argon gas. Step (3) Preparation of ZnI2@LLZTO electrolyte sheet A certain amount of ZnI2 powder is added into anhydrous ethanol to prepare a ZnI2 solution of a certain concentration, and the LLZTO sheet prepared in step (2) is placed into the ZnI2 solution to prepare a ZnI2@LLZTO electrolyte sheet; Step (4) Preparation of LAGP powder First, LiOH·H2O, Al2O3, GeO2 and NH4H2PO4 were completely mixed in a stoichiometric ratio by ball milling and heated at a certain temperature for a certain time to fully decompose LiOH·H2O and NH4H2PO4. Then, the above precursors were sintered to obtain Li 1.5 Al 0.5 Ge 1.5 (PO4)3 solid electrolyte powder, and finally, ball-milled and sieved to obtain LAGP powder; Step (5) Preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, using NMP (N-methylpyrrolidone) as a dispersant, the LAGP powder prepared in step (4) and PVDF (polyvinylidene fluoride) are mixed according to a weight ratio and magnetically stirred, and the slurry is applied to the surface of lithium foil by a drop coating method, and then dried under vacuum at 40° C. to obtain a lithium foil with a CPL coating; Step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh silicon powder and graphite powder, prepare raw materials of a certain mass ratio, mix the weighed silicon and graphite powders evenly to ensure that they can be fully mixed during the ball milling process, put the mixed raw materials into a ball tank, add an appropriate amount of agate balls into the ball mill, and at the same time, add anhydrous ethanol as a ball milling medium according to a certain material-liquid ratio to reduce the agglomeration of the raw materials. After the ball mill is sealed, put it into a planetary ball mill, set a certain speed and start the ball mill for ball milling to ensure that the raw materials are fully mixed and refined. Finally, put the ball-milled mixture into a vacuum drying oven for drying. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and use a sieve to screen it to obtain a Si / C composite negative electrode material; Step (7) Preparation of CaF2 First, C4H6CaO is added to deionized water, and then C6H5Na3O7 is added and stirred evenly. Next, NaBF4 is added to the solution, and the pH value of the solution is adjusted to a certain value with ammonia water. Finally, the mixed solution is transferred to a polytetrafluoroethylene reactor, and washed and dried by hydrothermal reaction to obtain CaF2 particles. Step (8) Preparation of Si / C-CPL-LCF composite lithium metal anode First, the CPL composite layer lithium foil prepared in step (5) is placed in a stainless steel container and heated, and the CaF2 nanopowder prepared in step (7) and the Si / C composite negative electrode material prepared in step (6) are added to molten lithium in a certain mass ratio, and are continuously stirred to react with the molten lithium, and finally a composite lithium metal negative electrode containing CaLi2 alloy, LiF and Si / C is obtained, which is referred to as Si / C-CPL-LCF composite lithium metal negative electrode; Step (9) Preparation of LFP composite cathode The active material, the conductive agent CNT (carbon nanotube) and the CSSE@20 homogeneous solution are mixed according to the mass ratio, and N-methylpyrrolidone (NMP) is used as the solvent to adjust the viscosity of the positive electrode slurry. After sufficient magnetic stirring, the slurry is evenly coated on the aluminum current collector. Secondly, the coated pole piece is transferred to an oven for vacuum drying to remove the ACN and NMP agents. Finally, after the pole piece is dried, the pole piece is cut into a circular pole piece by a punching machine, compacted, weighed, and vacuum dried again. The fully dried pole piece is transferred to a glove box for storage to obtain an LFP composite positive electrode; Step (10) Preparation of battery assembly First, the same electrode sheets such as Si / C-CPL-LCF and LFP are used for both positive and negative electrodes, among which Si / C-CPL-LCF and LFP electrodes are cut into round sheets using a puncher. Secondly, ZnI2@LLZTO is used as the electrolyte. Finally, the battery is assembled in a glove box filled with argon.
3. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 2, characterized in that: Step (1) Preparation of LLZTO powder LLZTO powder was prepared by solid phase method. 74-75g LiOH·H2O, 116-117g La2O3, 51-52g ZrO2, 13-14g Ta2O5 and 3-4g Al2O3 were added to the ball mill in sequence. Zirconia ball mill was used as ball milling beads. Isopropanol was used as solvent. LiOH·H2O was used in excess of 10-20% to compensate for the loss of lithium during high temperature calcination. Al2O3 was used as a sintering aid. The ball mill is carried out with a planetary ball mill at a rotation speed of 100-500r / min for 10-15h, and then the ball liquid is placed in an oven at 50-100℃ for drying for 36-48h. After drying, it is sieved and the ball-milled powder is calcined at high temperature, heated to 500-1000℃ at a rate of 1-5℃ / min, kept warm for 5-10h, cooled, and the product is continued to be ball milled for 36-48h, dried and sieved to obtain LLZTO powder.
4. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 3, characterized in that: Step (2) Preparation of LLZTO Sheet The LLZTO powder prepared in step (1) is pressed into a sheet at 100-500 KPa, sintered at 500-1000° C. for 1-5 h, and slowly cooled at 1-5° C. / min to obtain a dense LLZTO sheet with a diameter of ≈10-15 mm and a thickness of ≈0-1 mm. Finally, the prepared LLZTO sheet is polished in sequence using 200-400 mesh, 600-800 mesh, 1300-1500 mesh and 2800-3000 mesh sandpaper to control the thickness to ≈0-1 mm. The polished LLZTO electrolyte sheet is stored in a glove box filled with argon.
5. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 4, characterized in that: Step (3) Preparation of ZnI2@LLZTO electrolyte sheet 0.1-1.5 g of ZnI2 powder was added to anhydrous ethanol to prepare a ZnI2 solution, and a bare LLZTO sheet was placed in the ZnI2 solution for 5-10 s to prepare a ZnI2@LLZTO electrolyte sheet.
6. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 5, characterized in that: Step (4) Preparation of LAGP powder First, 1-2 mol LiOH·H2O, 0-1 mol Al2O3, 2-3 mol GeO2 and 2-3 mol NH4H2PO4 were completely mixed by ball milling and heated at 500-1000°C for 1-5 h to fully decompose LiOH·H2O and NH4H2PO4. Then, the precursors were sintered at 500-1000°C for 5-10 h to obtain Li 1.5 Al 0.5 Ge 1.5 The solid electrolyte powder of (PO4)3 is ball-milled for 12-24 hours and passed through a 100-500 mesh sieve to obtain LAGP powder.
7. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 6, characterized in that: Step (5) Preparation of CPL composite layer lithium foil In a glove box filled with argon protective gas, LAGP powder and PVDF are mixed in a weight ratio of 1:5-5:5 with NMP as a dispersant and magnetically stirred for 5-10 hours. The slurry is applied on the surface of lithium foil with a thickness of 100-450 μm by drop coating, and then dried under vacuum conditions at 30-50°C for 8-12 hours to obtain a lithium foil with a CPL coating.
8. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 7, characterized in that: Step (6) Si / C composite negative electrode material Use an electronic balance to accurately weigh the silicon powder and graphite powder, and mix the weighed silicon and graphite powders evenly according to the ratio of 1:9-4:6 after each group of raw materials to ensure that they can be fully mixed during the ball milling process. Put the mixed raw materials into the ball tank, add agate balls to the ball mill according to the ratio of ball to material of 1:1-5:1, and at the same time, add anhydrous ethanol as the ball milling medium according to the material-liquid ratio of 1:1-1:
5. The addition of anhydrous ethanol helps to reduce friction and heat during the ball milling process, and at the same time reduce the agglomeration of raw materials. After sealing the ball mill jar, put it into a planetary ball mill, set the speed to 100-500rpm and start the ball mill for ball milling. The ball milling time is 15-20h to ensure that the raw materials are fully mixed and refined. Put the ball-milled mixture into a vacuum drying oven and dry it at 50-100℃. The drying process must ensure that the mixture is completely dry to remove residual anhydrous ethanol. For the dried mixture, grind it to make its particles more uniform, and then use a 100-500 mesh sieve for sieving.
9. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 8, characterized in that: Step (7) Preparation of CaF2 First, add 1-5mmolC4H6CaO into 50-100mL deionized water, then add 5-15mmolC6H5Na3O7 and stir evenly, then add 1-5mmolNaBF4 into the solution, and adjust the pH value of the solution to 10-11 with ammonia water, transfer the mixed solution into a 50-100mL polytetrafluoroethylene reactor, perform hydrothermal reaction at 150-200℃ for 0-1h, and finally wash and dry to obtain CaF2 particles.
10. The high-performance solid-state battery containing the CPL-LCF composite lithium metal negative electrode material and the preparation method thereof according to claim 9, characterized in that: Step (8) Preparation of Si / C-CPL-LCF composite lithium metal anode The CPL composite layer lithium foil prepared in step (5) is placed in a stainless steel container and heated to 100-500°C, and the CaF2 nanopowder prepared in step (7) and the Si / C composite negative electrode material prepared in step (6) are added to the molten lithium in a mass ratio of 20:1-25:1, and are continuously stirred to react with the molten lithium, and finally a composite lithium metal negative electrode containing CaLi2 alloy and Si / C is obtained.
Citation Information
Cited By
Preparation method of solid electrolyte of lithium battery
CN120221771A